Preparation method and application of active calcium carbonate / ardealite composite material

Carbonization is made by adding reducing agent and CO2/N2 mixture to the treatment of white mud and phosphogypsum, and blending it with compound active agent and modified phosphogypsum to prepare activated calcium carbonate/phosphogypsum composite nanomaterials, and solving the problem of The problems of inefficiency and high cost in the prior art have been achieved, and efficient resource utilization and improved mechanical properties of biodegradable composite film materials have been achieved.

CN119391050APending Publication Date: 2025-02-07GUIZHOU MATERIAL IND TECH INSTITUE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411522523.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art has problems of inefficiency and high cost when utilizing phosphogypsum and white mud, making it difficult to achieve large-scale application and resource utilization.

Method used

Pretreatment is performed by adding a reducing agent to the white sludge suspended slurry, and then carbonization is carried out by introducing CO2/N2 mixed gas into the mixed slurry to improve the purity of calcium carbonate, and adding crystal form control agent to regulate the morphological structure. Then, the concentrated refined calcium carbonate was blended with the compound active agent and modified phosphogypsum, and after vacuum filtration and drying, an activated calcium carbonate/phosphogypsum composite nanomaterial was obtained.

Benefits of technology

The preparation of activated calcium carbonate/phosphogypsum composite nanomaterials has been achieved, with good dispersion, stability and compatibility, which can enhance the mechanical properties of biodegradable composite film materials and achieve the green color of white mud and phosphogypsum waste. Resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391050A_ABST
    Figure CN119391050A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an activated calcium carbonate / ardealite composite material. White mud suspension slurry is subjected to a series of treatments such as redox impurity removal, carbonization purification, crystal form regulation and control, activation modification and the like and then is subjected to a blending reaction with mechanical vertical mill modified phosphogypsum, and the active calcium carbonate / phosphogypsum composite nanomaterial with good dispersity, compatibility and stability is prepared. The prepared composite nano material is filled in a biodegradable material to prepare a composite film material, so that the mechanical property of the biodegradable composite film material can be enhanced and the raw material cost of a biodegradable matrix material can be reduced while the green circulating high-added-value application of the white mud and the phosphogypsum solid waste is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomaterials, and specifically relates to a preparation method and application of an active calcium carbonate / phosphogypsum composite material. Background Art

[0002] With the acceleration of industrialization, the treatment and utilization of industrial solid waste has become an urgent problem to be solved. In particular, the resource utilization of bulk industrial solid waste such as phosphogypsum and white mud can not only reduce environmental pollution, but also maximize economic benefits. Phosphogypsum is mainly derived from the by-products produced in the process of phosphate fertilizer production, while white mud is the solid waste produced in the process of limestone calcination. If these two materials are not effectively utilized, they will cause a serious burden on the environment.

[0003] At present, the comprehensive utilization of phosphogypsum and white mud has made some progress. For example, phosphogypsum can be converted into building materials, chemical products, etc. through technologies such as fluidized calcination. However, these methods are often energy-intensive, costly, and difficult to achieve large-scale application. In addition, the treatment of white mud also faces similar challenges. Although studies have explored methods for preparing light calcium carbonate using white mud, these methods also have problems of low efficiency and high cost. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an activated calcium carbonate / phosphogypsum composite nanomaterial.

[0007] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing an activated calcium carbonate / phosphogypsum composite nanomaterial, characterized in that: it comprises:

[0008] Adding a reducing agent to the white mud suspension slurry, and ultrasonically washing and screening to remove impurities before treatment, then passing a CO2 / N2 mixed gas into the mixed slurry to carbonize it to a pH value less than 7 to improve the purity of calcium carbonate, and adding a crystal control agent to regulate the morphology and structure of calcium carbonate to obtain concentrated and refined calcium carbonate;

[0009] The concentrated refined calcium carbonate slurry is mixed with the compound active agent and stirred at high speed, and then the modified phosphogypsum is added for blending reaction. After being naturally cooled, the filter cake is obtained by vacuum filtration. The filter cake is dried in a 60°C forced air drying oven, and then processed by a pulverizer and passed through a 200-mesh sieve to obtain an activated calcium carbonate / phosphogypsum composite nanomaterial.

[0010] As a preferred embodiment of the preparation method of the present invention, the reducing agent is any one of sodium bisulfite, calcium sulfite, sodium thiosulfate, sodium dithionite and hydrazine hydrate.

[0011] As a preferred embodiment of the preparation method of the present invention, the crystal directing agent is at least one of glucose, mannan, trehalose, polygalactose, polyfructose, cellulose and starch, and its addition amount is 0.1-0.6% of the mass of calcium carbonate.

[0012] As a preferred embodiment of the preparation method of the present invention, the mixed gas flow rate is 3-6 L / min, and the gas flow ratio CO2 / N2=1:3-5.

[0013] As a preferred embodiment of the preparation method of the present invention, the compound active agent is a compound of any of sodium polyacrylate, sodium stearate, phosphate (salt), sodium dodecylbenzene sulfonate, myristic acid, lauric acid, and palmitic acid, and the added amount is 1 to 8% of the mass of calcium carbonate.

[0014] As a preferred embodiment of the preparation method described in the present invention, the modified phosphogypsum is phosphogypsum and a dispersant modified by a mechanical vertical mill, and the dispersant is any one of polyether modified silicone oil, vinyl mono-terminated polydimethylsilane, vinyl di-terminated polydimethylsilane, methyltriethoxysilane oligomer, and ethyltrimethoxysilane oligomer, and the added amount thereof is 0.1 to 1% of the mass of the phosphogypsum.

[0015] As a preferred solution of the preparation method of the present invention, the phosphogypsum is treated by mechanical vertical mill to remove impurities, and its particle size is less than 2000 mesh, and the addition amount is 10-30% of the mass of calcium carbonate.

[0016] Another object of the present invention is to overcome the deficiencies in the prior art and provide an activated calcium carbonate / phosphogypsum composite nanomaterial.

[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of an activated calcium carbonate / phosphogypsum composite material in filling a biodegradable composite film material.

[0018] As a preferred embodiment of the application of the present invention, the method for preparing the biodegradable composite film material comprises:

[0019] The active calcium carbonate / phosphogypsum composite nanomaterial, the biodegradable matrix material, the chain extender, the nucleating agent and the lubricant mixed material are extruded into granules in a twin-screw extruder, and blown into a film to obtain a biodegradable composite film material;

[0020] Among them, the temperature of zone one of the twin-screw extruder is 135-155°C, the temperature of zone two is 145-165°C, the temperature of zone three is 155-185°C, the temperature of zone four is 155-185°C, the temperature of zone five is 155-185°C, and the head speed is 1000-2000RPM.

[0021] The temperature of barrel zone 1 of the film blowing machine is 135-155°C, the temperature of barrel zone 2 is 155-185°C, the temperature of barrel zone 3 is 155-185°C, the temperature of mold zone 1 is 135-155°C, and the temperature of mold zone 1 is 135-155°C; the screw speed of the film blowing machine is 600-1000RPM, the traction speed is 350-550RPM, and the winding speed is 450-650RPM.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention activates and modifies the refined calcium carbonate from white mud, and then blends it with the phosphogypsum after the vertical mill to coat the activated calcium carbonate on the phosphogypsum to form an activated calcium carbonate / phosphogypsum composite nanomaterial. The obtained composite material has good dispersibility, stability and compatibility.

[0024] (2) The preferred dispersant of the present invention, one of polyether-modified silicone oil, vinyl mono-terminated polydimethylsilane, vinyl di-terminated polydimethylsilane, methyltriethoxysilane oligomer, and ethyltrimethoxysilane oligomer, is treated with phosphogypsum by mechanical vertical mill modification to improve the dispersibility and compatibility of phosphogypsum.

[0025] (3) The composite material prepared by the present invention is used as a filler for a biodegradable matrix material to enhance the mechanical properties of the biodegradable composite material. A high filling amount can reduce the cost of raw materials while realizing the green resource utilization of white mud and phosphogypsum waste, which is of great significance to environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0027] Figure 1Scanning electron microscope (SEM) image of biodegradable film material filled with composite nanomaterials. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0030] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0031] The sources of raw materials used in the present invention are: white mud comes from Guizhou Xingchi Environmental Protection Technology Co., Ltd., and phosphogypsum comes from Guizhou Wengfu Chemical Co., Ltd.

[0032] Instruments used in the embodiments of the present invention:

[0033] The test method of D10, D50 and D90 in the present invention is as follows: the test means is a laser particle size distribution instrument, and the test method is to adopt wet dispersion technology, mechanical stirring to evenly disperse the sample, ultrasonic high-frequency vibration to fully disperse the agglomerated particles, and an electromagnetic circulation pump to evenly distribute large and small particles in the entire circulation system, and the quality stability of the product performance is reflected from the width of the particle size distribution.

[0034] The test methods for tensile strength and elongation at break in the present invention are as follows:

[0035] The thickness and width of the film sample should be measured at three points within the gauge length, and the arithmetic mean should be taken; the thickness should be accurate to 0.001mm, and the width should be accurate to 0.1mm. The film should be cut into 10×150mm samples in the horizontal and vertical directions, and the samples should be placed in the two clamps of the testing machine, so that the longitudinal axis of the sample coincides with the center line of the upper and lower clamps, and the tightness should be appropriate to prevent the sample from slipping and breaking in the clamps; start the testing machine at a tensile speed of 50mm / min to conduct the test. After the sample breaks, read the required load and the corresponding elongation value between the gauge lines.

[0036] Example 1

[0037] This embodiment is the preparation of white mud refined calcium carbonate / phosphogypsum composite material, comprising the following steps:

[0038] (1) White mud refined calcium carbonate

[0039] The white mud was prepared into a suspension slurry, 500 g of the slurry was measured and placed in a carbonization reactor (the reactor temperature was 30°C), the stirring speed was set to 400 r / min, 0.05% sodium bisulfite reducing agent was added to the reactor, and the reaction was stirred for 60 min to remove impurities in the white mud.

[0040] A membrane dispersion microreactor is then used to disperse a mixed gas of CO2 and N2 into the slurry, and 0.2% glucose crystal form controller is added to adjust the morphology of calcium carbonate. The residual alkaline components in the white mud are removed by carbonization reaction through gas-liquid combination of the mixed gas and the slurry, thereby improving the purity of calcium carbonate. The carbonization is completed when the pH value of the slurry is less than 7. The calcium carbonate slurry is allowed to stand overnight to obtain a concentrated and refined calcium carbonate, which is then subjected to a slight dehydration treatment by filter press.

[0041] (2) Activated calcium carbonate / phosphogypsum composite materials

[0042] After the concentrated calcium carbonate slurry is heated to 75°C, 4% of the weight of calcium carbonate phosphate (salt) and palmitic acid composite active agent are added to the slurry, and after high-speed stirring for 30 minutes, 10% of modified phosphogypsum is added and mixed with it for 60 minutes. After naturally cooling, the filter cake is obtained by vacuum filtration, and the filter cake is dried in a 60°C forced air drying oven, and then processed by a crusher and passed through a 200-mesh sieve to obtain an activated calcium carbonate / phosphogypsum composite nanomaterial.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that the addition amount of the phosphate (salt) and palmitic acid compound active agent is replaced by 2% instead of 4%, and the remaining steps are the same as those in embodiment 1 to prepare a composite nanomaterial.

[0045] The particle size distribution effect of the composite nanomaterials was determined, see Table 1.

[0046] Table 1

[0047] condition D10 D50 D90 Example 1 0.45 1.56 4.13 Example 2 0.73 3.32 7.64

[0048] As can be seen from Table 1, when the addition amount of the phosphate (salt) and palmitic acid compound active agent is replaced by 4% to 2%, the particle size distribution of the activated calcium carbonate / phosphogypsum composite material is relatively wide, while the particle size distribution of Example 1 is more reasonable, indicating that the low addition amount of the compound active agent cannot fully activate and modify the calcium carbonate, resulting in poor product quality stability.

[0049] Example 3

[0050] The difference between this embodiment and embodiment 1 is that the addition amount of the phosphate (salt) and palmitic acid compound active agent is replaced by 8% instead of 4%, and the remaining steps are the same as those in embodiment 1 to prepare a composite nanomaterial.

[0051] The particle size distribution effect of the composite nanomaterials was determined, see Table 2.

[0052] Table 2

[0053] condition D10 D50 D90 Example 1 0.45 1.56 4.13 Example 3 1.25 4.42 8.40

[0054] It can be seen from Table 2 that when the addition amount of the compounded active agent is 8%, the particle size distribution is wider, indicating that the agglomeration problem is caused by the excess of the compounded active agent, which makes the product quality stability worse.

[0055] Example 4

[0056] The difference between this embodiment and embodiment 1 is that the phosphate (salt) and palmitic acid compound active agent is replaced by sodium stearate, and the remaining steps are the same as those in embodiment 1 to prepare a composite nanomaterial.

[0057] The particle size distribution effect of the composite nanomaterials was determined, see Table 3.

[0058] Table 3

[0059]

[0060]

[0061] It can be seen from Table 3 that when the compound active agent is changed to a single active agent, sodium stearate, the particle size distribution effect of the composite nanomaterial particles of Example 4 is obviously inferior to that of Examples 1 to 3, and the product quality stability of Examples 1 to 3 is relatively better.

[0062] Example 5

[0063] The difference between this embodiment and embodiment 1 is that the modified phosphogypsum is replaced by unmodified phosphogypsum, and the remaining steps are the same as those in embodiment 1 to prepare a composite nanomaterial.

[0064] The particle size distribution effect of the composite nanomaterials was determined, see Table 4.

[0065] Table 4

[0066] condition D10 D50 D90 Example 1 0.45 1.56 4.13 Example 4 1.50 8.75 15.70

[0067] It can be seen from Table 4 that when the modified phosphogypsum is replaced by unmodified phosphogypsum, the particle size distribution of the composite nanomaterial obtained is very wide, mainly due to the poor dispersibility of the unmodified phosphogypsum.

[0068] Example 6

[0069] The difference between this embodiment and embodiment 1 is that the addition amount of modified phosphogypsum is replaced by 30% instead of 10%, and the remaining steps are the same as those in embodiment 1 to obtain a composite nano material.

[0070] The particle size distribution effect of the composite nanomaterials was determined, see Table 5.

[0071] Table 5

[0072] condition D10 D50 D90 Example 1 0.45 1.56 4.13 Example 5 0.83 3.45 6.51

[0073] It can be seen from Table 5 that when the addition amount of modified phosphogypsum is increased to 30%, the particle size distribution of the prepared composite nanomaterial is relatively reasonable, but there is a situation where the phosphogypsum is not completely coated by calcium carbonate, which affects the overall performance of the activated calcium carbonate / phosphogypsum composite nanomaterial.

[0074] Example 7

[0075] This embodiment uses the composite nanomaterials prepared in Examples 1 to 6 to prepare biodegradable composite film materials, including the following steps:

[0076] Active calcium carbonate / phosphogypsum composite nanomaterials, biodegradable matrix materials, chain extenders, nucleating agents and lubricant mixed materials are extruded and granulated in a twin-screw extruder, and blown into films to obtain biodegradable composite film materials.

[0077] Among them, the temperature of zone one of the twin-screw extruder is 135-155°C, the temperature of zone two is 145-165°C, the temperature of zone three is 155-185°C, the temperature of zone four is 155-185°C, the temperature of zone five is 155-185°C, and the head speed is 1000-2000RPM.

[0078] The temperature of barrel zone 1 of the film blowing machine is 135-155°C, the temperature of barrel zone 2 is 155-185°C, the temperature of barrel zone 3 is 155-185°C, the temperature of mold zone 1 is 135-155°C, and the temperature of mold zone 1 is 135-155°C; the screw speed of the film blowing machine is 600-1000RPM, the traction speed is 350-550RPM, and the winding speed is 450-650RPM.

[0079] The mechanical properties of the composite nanomaterials prepared in Examples 1 to 6 for preparing biodegradable composite film materials are shown in Table 6.

[0080] Table 6

[0081]

[0082] From the mechanical properties comparison in Table 6, it can be seen that the selection and addition amount of calcium carbonate compound active agent in the composite nanomaterial have a great influence on the mechanical properties of the biodegradable composite film material; at the same time, it is found that the modification effect of phosphogypsum also has a great influence on the mechanical properties of the biodegradable composite film material.

[0083] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing an activated calcium carbonate / phosphogypsum composite material, characterized in that: include, Adding a reducing agent to the white mud suspension slurry, and ultrasonically washing and screening to remove impurities before treatment, then passing a CO2 / N2 mixed gas into the mixed slurry to carbonize it to a pH value less than 7 to improve the purity of calcium carbonate, and adding a crystal control agent to regulate the morphology and structure of calcium carbonate to obtain concentrated and refined calcium carbonate; The concentrated refined calcium carbonate slurry is mixed with the compound active agent and stirred at high speed, and then the modified phosphogypsum is added for blending reaction. After being naturally cooled, the filter cake is obtained by vacuum filtration. The filter cake is dried in a 60°C forced air drying oven, and then processed by a pulverizer and passed through a 200-mesh sieve to obtain an activated calcium carbonate / phosphogypsum composite nanomaterial.

2. The preparation method according to claim 1, characterized in that: The reducing agent is any one of sodium bisulfite, calcium sulfite, sodium thiosulfate, sodium dithionite and hydrazine hydrate, and the addition amount thereof is 0.01-0.1% of the mass of the white mud.

3. The preparation method according to claim 1, characterized in that: The crystal form control agent is at least one of glucose, mannan, trehalose, polygalactose, polyfructose, cellulose and starch, and the added amount thereof is 0.1-0.6% of the mass of calcium carbonate.

4. The preparation method according to claim 1, characterized in that: The mixed gas flow rate is 3-6 L / min, and the gas flow ratio CO2 / N2=1:3-5.

5. The preparation method according to claim 1, characterized in that: The compound active agent is a compound of any of sodium polyacrylate, sodium stearate, phosphate (salt), sodium dodecylbenzene sulfonate, myristic acid, lauric acid and palmitic acid, and the added amount is 1-8% of the mass of calcium carbonate.

6. The preparation method according to claim 1, characterized in that: The modified phosphogypsum is prepared by modifying phosphogypsum and a dispersant through a mechanical vertical mill. The dispersant is any one of polyether-modified silicone oil, vinyl mono-terminated polydimethylsilane, vinyl di-terminated polydimethylsilane, methyltriethoxysilane oligomer, and ethyltrimethoxysilane oligomer, and the added amount thereof is 0.1-1% of the mass of the phosphogypsum.

7. The preparation method according to claim 1, characterized in that: The phosphogypsum is treated by mechanical vertical grinding to remove impurities and modification, and its particle size is less than 2000 meshes, and the addition amount is 10-30% of the mass of calcium carbonate.

8. The activated calcium carbonate / phosphogypsum composite nanomaterial obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the activated calcium carbonate / phosphogypsum composite material as claimed in claim 8 in filling biodegradable composite film materials.

10. The use according to claim 9, characterized in that: The preparation method of the biodegradable composite film material, include, The active calcium carbonate / phosphogypsum composite material, the biodegradable matrix material, the chain extender, the nucleating agent and the lubricant mixed material are extruded and granulated in a twin-screw extruder, and blown into a film to obtain a biodegradable composite film material; Among them, the temperature of zone one of the twin-screw extruder is 135-155°C, the temperature of zone two is 145-165°C, the temperature of zone three is 155-185°C, the temperature of zone four is 155-185°C, the temperature of zone five is 155-185°C, and the head speed is 1000-2000RPM. The temperature of barrel zone 1 of the film blowing machine is 135-155°C, the temperature of barrel zone 2 is 155-185°C, the temperature of barrel zone 3 is 155-185°C, the temperature of mold zone 1 is 135-155°C, and the temperature of mold zone 1 is 135-155°C; the screw speed of the film blowing machine is 600-1000RPM, the traction speed is 350-550RPM, and the winding speed is 450-650RPM.